2018
DOI: 10.1103/physreve.98.023002
|View full text |Cite
|
Sign up to set email alerts
|

Fiber-bundle model with time-dependent healing mechanisms to simulate progressive failure of snow

Abstract: Snow is a heterogeneous material with strain-and/or load-rate-dependent strength. In particular, a transition from ductile-to-brittle failure behavior with increasing load rate is observed. The rate-dependent behavior can partly be explained with the existence of a unique healing mechanism in snow that stems from its high homologous temperature (temperature close to melting point). As soon as broken elements in the ice matrix get in contact, they start sintering and the structure may regain strength. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 43 publications
0
35
0
Order By: Relevance
“…Hence, our model successfully captures the so-called strain-rate dependency of snow [ 31 ]. This increase in snow strength with decreasing loading rate was also well captured by the fiber bundle model of Reiweger et al [ 28 ] and Capelli et al [ 4 ] (also including viscous stress relaxation), but they did not investigate the effect of the loading angle and sintering, simultaneously.…”
Section: Discussionmentioning
confidence: 59%
“…Hence, our model successfully captures the so-called strain-rate dependency of snow [ 31 ]. This increase in snow strength with decreasing loading rate was also well captured by the fiber bundle model of Reiweger et al [ 28 ] and Capelli et al [ 4 ] (also including viscous stress relaxation), but they did not investigate the effect of the loading angle and sintering, simultaneously.…”
Section: Discussionmentioning
confidence: 59%
“…Data are thus required to describe the mismatch between the weak layer and the slab or the softening behavior prior to failure (Gaume et al, 2018). During natural release, deformation in the snowpack takes place at longer times scales (>1 s), and Capelli et al (2018a) showed that healing of broken bonds or viscoelastic load redistribution are important processes for failure at lower rates. Hence, to model natural release, knowledge of the sintering behavior of different weak layer grain types is relevant.…”
Section: Introductionmentioning
confidence: 99%
“…The higher strength and the higher strain at equal stress for low loading rates observed for snow were reproduced by the FBM. The strain rate divergence is caused by a divergence of the number of intact fibers carrying load and the resulting increase of the load per fiber (see also the discussion about the order parameter in Capelli, Reiweger, Lehmann, et al, 2018). However, at low loading rates the model shows a divergence of the strain rate that was not observed in the experiments (Figure 1b).…”
Section: Comparison Of Fbm and Experimental Failure Characteristicsmentioning
confidence: 85%
“…The probability of sintering increases with the number of broken fibers N broken , since we assume that in order to form a new bond, a broken fiber needs to meet another broken one. The effects of sintering speed on the damage process are discussed in more detail in Capelli, Reiweger, Lehmann, et al (2018). The strength of a new ice bond increases with time.…”
Section: Model Calibrationmentioning
confidence: 99%
See 1 more Smart Citation